Influence of Sintering Temperature on the Properties of in-Situ Carbide-Reinforced Hybrid Copper-Based Composite - Le, Minh Hai; Duong, Ngoc Binh; Tran, Duc Huy (Old Journal, 2017)
The aim of this research is to investigate the influence of the sintering temperature on the properties of the in-situ carbide (Nb,Ti)C in a copper matrix synthesized via mechanical alloying and powder metallurgy from elemental powders of Cu, Nb, Ti and graphite. The mixture of starting powders with compositions corresponding to Cu-15vol.% (Nb, Ti)C was mechanical alloyed using a planetary ball mill for 20 hours. The as-milled powders then were uniaxial cold pressed at compaction pressure of 800 MPa and sintered in a vacuum sintering furnace for 1 hour at different temperatures from 700 to 1000oC. The obtained results revealed that sintering temperature was an important factor to produce a bulk in-situ Cu-(Nb, Ti)C composite. Higher sintering temperature led to an increase in density and electrical conductivity of the bulk composite with a decrease in microhardness as a result of higher rate of recrystallization and the elimination of dislocation at higher sintering temperature.